Growth performance and carcass yield of broiler chicken feed diets with blends of phytogenic additives - Koiyama, Natália Thaís Gonçalves; Rosa, Alexandre Pires; Padilha, Marília Terezinha Sangoi; Boemo, Lenise Schröder; Scher, Anelcir; Melo, Andréia Medianeira da Silva; Fernandes, Mariane de Oliveira (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effect of blending phytogenic additives in broiler chicken diets on their growth performance and carcass yield. Six hundred and sixty mixed-sex broiler chicks, from 1 to 42 days of age, were evaluated in a completely randomized design, with five treatments and six replicates of 22 chicks each (11 males and 11 females). Besides the control, treatments with antibiotic (10 ppm virginiamycin) or with blends of phytogenic additives were evaluated: blend A, 150 ppm of a mixture of essential oils from rosemary, clove, ginger, and oregano; blend B, 150 ppm of a mixture of essential oils from cinnamon, sage, white thyme, and copaiba oil‑resin; and blend A+B, a mixture of 50% blend A and 50% blend B. Blend B provided the highest weight gain and better feed conversion rate at the period of 36 to 42 days of age. In the total experimental period, the antibiotic and blend B provided higher broiler weight gain. Feed intake was higher with the antibiotic than with the control. Blend A+B and the control treatment provided higher thigh+drumstick yield and higher relative weight of spleen. The blends B and A+B have potential as performance enhancers for broiler chicken.